Failure mode, deformability and strength of masonry walls - Mohamad, Gihad (2012)
For materials such as concrete, the understanding of the failure mode, deformability and strength of block masonry walls are important to simulate the behaviour of the assembly. Still now, there are difficulties on determine experimentally results of the interaction between the materials, as concrete block, mortar and the interface between vertical and bedding joint. Because of this, experimental tests of masonry walls were built to get the deformability, failure modes and compressive strength of the masonry. Experimental tests of tensile and compression on blocks had been done. With the conclusion of experimental tests it is possible to verify that the vertical mortar joint was the main responsible for initiated the failure mechanisms of masonry and further studies of masonry built with high adherence mortar are necessary to improve the ratio between compressive strength of wall and blocks.